Development of a mechanical instrument evalute biomechanically the spinal coloumn in pregnant women - Quaresma, Cláudia (2013)
The incidence of problems related to rachialgiae is so frequent and usual that it must be studied as if it were an epidemic and social disease (Knoplich, 2003). Instruments that evaluate the spinal column in a standing position, in a global way, are needed to attain a better insight into this problem. This work presents a completely safe instrument to assess the evolution of all the vertebra locations throughout time, in order to study the biomechanical changes in women during pregnancy. A mechanical system, registered as Vertebral Metrics, with the objective of evaluating the curvatures and lateral deviations of the spinal column in the standing position was built. A measuring part, which is the body of the instrument, and a supporting part, where the previous part is mounted, constitute the new non-invasive instrument. The measuring part consists of 17 identical adjustable mechanical blocks that allow us to reproduce the position of each vertebra of the spinal column, from the first cervical vertebra o the first sacral vertebra. Vertebral Metrics was originally planned and built to be applied to pregnant women. However, after redefining dimensions of the different parts it can be applied to any type of population, in the future.